Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2014
DOI: 10.1145/2556288.2557162
|View full text |Cite
|
Sign up to set email alerts
|

Supporting learners in collecting and exploring data from immersive simulations in collective inquiry

Abstract: Digitally augmented physical spaces (e.g., smart classrooms) offer opportunities to engage students in novel and potentially transformative learning experiences. This paper presents an immersive rainforest simulation and collective inquiry activity where students collect observational data from the environment and explore their peers' data through large visualization displays and personal mobile devices. Two iterations of the design were tested, which resulted in higher quality student explanations constructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…Some studies have shown an immersive simulation environment that involves large interactive displays in classes for collective inquiry from students based on their experiences and observations. Compared to the traditional inquiry-based system, the new spaces offer new types of learning experiences that serve to engage students with science concepts that have traditionally been taught through more passive or less advanced forms of interaction (Lui et al 2014). In this respect, learners are turned into active participants because of the surrounding physical environment, which serves to motivate learners to think, reflect and drive their own understanding (Price & Rogers 2004).…”
Section: Smart Pervasive Learning Spacesmentioning
confidence: 99%
See 4 more Smart Citations
“…Some studies have shown an immersive simulation environment that involves large interactive displays in classes for collective inquiry from students based on their experiences and observations. Compared to the traditional inquiry-based system, the new spaces offer new types of learning experiences that serve to engage students with science concepts that have traditionally been taught through more passive or less advanced forms of interaction (Lui et al 2014). In this respect, learners are turned into active participants because of the surrounding physical environment, which serves to motivate learners to think, reflect and drive their own understanding (Price & Rogers 2004).…”
Section: Smart Pervasive Learning Spacesmentioning
confidence: 99%
“…The augmented spaces can adopt a variety of learning methods. A study shows that learners would be able to collect, observe and explore data from the equipped augmented setting through visualisation displays and a variety of personal gadgets (Lui et al 2014). As a result, collective information and various visualisations generated from the ambient environment can improve users' experience and allow for more engaging teaching and learning methods.…”
Section: Augmented Physical Environment (Ape)mentioning
confidence: 99%
See 3 more Smart Citations